Adaptation of Cowpea (Vigna unguiculata (L.) Walp.) to Water Deficit during Vegetative and Reproductive Phases Using Physiological and Agronomic Characters - Ezin, Vincent; TOSSE, Marie-Madeleine; Chabi, Ifagbe´mi Bienvenue; Ahanchede, Adam (My University, 2021)
Cowpea (Vigna unguiculata (L.) Walp.) is an important commodity in West Africa. Its seeds are a valuable source of protein, vitamins, and income for humans. However, cowpea cultivation in Benin faces climatic constraints such as water stress caused by a prolonged absence of rain during the rainy season. )us, this work aims at selecting cowpea varieties that can be cultivated in times of drought without compromising their yields and yield components. Twenty cowpea varieties were used, including 17 improved cultivars and 3 landraces. )e experiment was conducted at the International Institute of Tropical Agriculture in Benin and laid at a split-plot design with four replicates. Each genotype was exposed to three water treatments: fully irrigated control, vegetative stress (when plants were 23 days old, drought stress was imposed for 30 days), and reproductive stress (once the first flowers were observed, water stress was imposed for 30 days). )e results showed that photochemical yield, chlorophyll content, and relative water content were reduced under water deficit at the vegetative and reproductive stages. But there were no significant differences in proline content among cowpea varieties. Agronomic traits such as number of days to flowering, number of pods, yield per plant, the weight of 100 seeds, and harvest time showed significant differences under water stress. Overall, the landraces and cultivars including Kpodjiguegue, KVX 61-1, and IT 06-K-242-3 were the most tolerant to drought stress at the vegetative and reproductive stages and could potentially be used in breeding programs to improve drought tolerance of cowpeas.
Keywords: leguminous crop; water deficit; resistance; improvement; climate change